The role of data analysis in improving the transparancy accounting information - Khairul Amri Hasibuan; Iskandar Muda (Indonesia Accounting Research Journal, 2025)
This research aims to examine how accounting information transparency has undergone transformation and development in the digital era in every organization. The results of the study show that sophisticated data analysis techniques, adoption of modern data analysis technology, ERP implementation, understanding of new technologies, data analytical skills, BI application and the use of big data have a significant effect on the transparency of accounting information. The methodology of this research uses a qualitative descriptive approach by collecting data through literature review from various relevant sources, the data sources of this research include articles, journals, books, research reports and other sources.